2015
DOI: 10.1186/s12889-015-2400-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with repeat induced abortion in Kenya

Abstract: BackgroundOver six million induced abortions were reported in Africa in 2008 with over two million induced abortions occurring in Eastern Africa. Although a significant proportion of women in the region procure more than one abortion during their reproductive period, there is a dearth of research on factors associated with repeat abortion.MethodsData for this study come from the Magnitude and Incidence of Unsafe Abortion Study conducted by the African Population and Health Research Center in Kenya in 2012. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
45
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 19 publications
(31 reference statements)
18
45
7
1
Order By: Relevance
“…The findings indicated the need for effective contraception skills improvement and objective treatment of PAC patients by service providers. This role of effective contraception is in line with studies showing high rates of repeat induced abortion among women across all age groups …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings indicated the need for effective contraception skills improvement and objective treatment of PAC patients by service providers. This role of effective contraception is in line with studies showing high rates of repeat induced abortion among women across all age groups …”
Section: Discussionsupporting
confidence: 83%
“…This role of effective contraception is in line with studies showing high rates of repeat induced abortion among women across all age groups. 21,22 The capacity of the care provider is of prime importance when offering PAC services. 1 All PAC patients must receive FP services to enable them to space or limit future pregnancies, and so prevent further unwanted pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of several studies [37,38,39] are similar to those of this study. Namely, there were notable rate differences of induced abortions in different contextual and informed choice factors.…”
Section: Discussionsupporting
confidence: 92%
“…The determinants of pregnancy termination are highly correlated with socioeconomic, demographic, behavioral factors of households and cultural factors. Several studies have investigated maternal age, and education is found to be strongly correlated with pregnancy termination [10][11][12][13][14]. Level of educational attainment is directly linked with pregnancy termination.…”
Section: Introductionmentioning
confidence: 99%